THE EFFECT OF VITAMIN D ON THE DEVELOPMENT OF IMMUNITY IN CHILDREN: A REVIEW OF MODERN RESEARCH (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Vitamin D plays a key role in regulating the immune system, influencing innate and adaptive immune mechanisms. Vitamin D deficiency in children is associated with increased susceptibility to infectious diseases, as well as with the development of autoimmune disorders. This review article presents current research that reveals the role of vitamin D in the formation of the immune response in children.